A possible influence of extracellular polysaccharides on the analysis of intracellular metabolites from Trichoderma harzianum grown under carbon-limited conditions. Issue 5 (May 2021) - Gelain, Lucas; Geraldo da Cruz Pradella, José; Carvalho da Costa, Aline; van der Wielen, Luuk; van Gulik, Walter M.
Abstract: Intracellular metabolites were evaluated during the continuous growth of Trichoderma harzianum P49P11 under carbon-limited conditions. Four different conditions in duplicate were investigated (10 and 20 g/L of glucose, 5.26/5.26 g/L of fructose/glucose and 10 g/L of sucrose in the feed). Differences in the values of some specific concentrations of intracellular metabolites were observed at steady-state for the duplicates. The presence of extracellular polysaccharide was confirmed in the supernatant of all conditions based on FT-IR and proton NMR. Fragments of polysaccharides from the cell wall could be released due to the shear stress and since the cells can consume them under carbon-limited conditions, this could create an unpredictable carbon flow rate into the cells. According to the values of the metabolite concentrations, it was considered that the consumption of those fragments was interfering with the analysis. Graphical abstract: Image 1 Highlights: Analysis of intracellular metabolites from Trichoderma harzianum P49P11. Production of extracellular polysaccharides under carbon-limited conditions. Polysaccharide production could have influenced the analysis of metabolite concentrations. Average values of the conditions could represent the intracellular environment.